Strong Convergence for a Strongly Quasi-Nonexpansive Sequence in Hilbert Spaces - Satit Saejung; Kanokwan Wongchan (Abstract and Applied Analysis)
We prove a strong convergence theorem for strongly quasi-nonexpansive sequence of mappings in Hilbert spaces. Moreover, we can improve the recent results of Tian and Jin (2011). We also give a simple proof of Marino-Xu’s result (2006).